The propagation and ignition of the finely dispersed coal-water aerosol; Fuel; Vol. 263 - Egorov R. I. Roman Igorevich; Tkachenko P. P. Pavel Petrovich; Taburchinov R. I. Roman Iljich; Chulkov A. O. Arseniy Olegovich (2020, 2020)
Title screen